2011
DOI: 10.4103/0970-9290.84303
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of periodontal status and bone mineral density in postmenopausal women: A digital radiographic and quantitative ultrasound study

Abstract: Calcaneal BMD was related to alveolar bone loss and, to a lesser extent, to clinical attachment loss, implicating postmenopausal bone loss as a risk indicator for periodontal disease in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…With the advent of ultrasound, it is now possible to measure bone density with a small, portable ultrasound unit designed exclusively for bone density testing. 14,[16][17][18] Distribution of participants in the present study is in line with other cross sectional studies by Al Habashneh et al 19 where 400 participants were included and by Aspalli et al, 20 which included 200 subjects and other cross sectional studies, where in only selected 50 periodontitis patients by Ryan et al 21 and 18 osteoporotic and 16 nonosteoporotic postmenopausal Taiwanese women were selected by Wactawski-Wende. 22 In the present study, the prevalence of periodontal disease in osteoporotic subjects were 20 (9.09%) healthy, 70 (31.81%) were with gingivitis, 120 (54.5%) were with periodontitis and 10 (4.5%) were edentulous patients.…”
Section: Discussionsupporting
confidence: 81%
“…With the advent of ultrasound, it is now possible to measure bone density with a small, portable ultrasound unit designed exclusively for bone density testing. 14,[16][17][18] Distribution of participants in the present study is in line with other cross sectional studies by Al Habashneh et al 19 where 400 participants were included and by Aspalli et al, 20 which included 200 subjects and other cross sectional studies, where in only selected 50 periodontitis patients by Ryan et al 21 and 18 osteoporotic and 16 nonosteoporotic postmenopausal Taiwanese women were selected by Wactawski-Wende. 22 In the present study, the prevalence of periodontal disease in osteoporotic subjects were 20 (9.09%) healthy, 70 (31.81%) were with gingivitis, 120 (54.5%) were with periodontitis and 10 (4.5%) were edentulous patients.…”
Section: Discussionsupporting
confidence: 81%
“…However, a couple of studies have suggested an association between systemic osteoporosis and periodontal disease1718. Vishwanath et al 201119 showed weak but negative association between BMD and periodontal status. In contrast to the above findings, Pepelassi et al 201220 found higher bleeding scores in osteoporotic patients than in patients with normal bone mineral density.…”
Section: Discussionmentioning
confidence: 97%
“…While it is still controversial whether osteoporosis has a detrimental effect on the jawbones, growing evidence from pre-clinical and clinical studies seems to suggest a correlation between bone density measured at different systemic skeletal sites and at the jawbones, [266][267][268][269][270][271][272][273][274][275] and that osteoporosis is associated with a reduced bone quality and increased cortical porosity in the jaws. [276][277][278][279][280][281] As such, a review has suggested that osteoporotic bone should be regarded as equivalent to Type IV according to Lekholm and Zarb 282 classification and that clinicians may consider a longer healing period for implant osseointegration before prostheses insertion in patients with osteoporosis.…”
Section: Osteoporosismentioning
confidence: 99%